ANALISIS DETERMINAN KEPATUHAN SISWA DALAM PENERAPAN KEBIJAKAN KAWASAN TANPA ROKOK DI SMAN 31 JAKARTA TAHUN 2023 - Jahira Fajri Madani (2024)
Smoking behaviour among adolescents is increasing and uncontrollable. In controlling smoking behavior, the government has established a smoke-free area policy as stated in Republic of Indonesia Law No. 36 of 2009 concern Health Article 115 in several places, including teaching and learning centers. The purpose of this study was to analyze the determinants of student compliance in implementing smoke-free area policy at 31 Senior High School. The study was conducted with a cross sectional design, the sample size was 110 students, which was determined using a simple random sampling technique. Data analysis used univariate, bivariate with chi square and multivariate with multiple logistic regression. The results of the analysis showed that there was a significant relationship between knowledge (p-value = 0,027), attitude (p-value = 0,008), and socialization (p-value = 0,001). Socialization is the most influencing factor with student compliance in implementing the policy (OR = 12,855), meaning that students with good socialization have a 12 times higher chance of compliance than students with less socialization. Schools can increase socialization activities in smoke-free areas for all students so that a smoke-free school environment can be created.